Morton Smith and Gershom Scholem, correspondence 1945-1982 - Scholem, Gershom, 1897-1982 (Jerusalem studies in religion and culture ;, 2008)
The American historian of ancient religions Morton Smith (1915-1991), had studied with the great scholar of Jewish mysticism Gershom Scholem (1897-1982), while in Jerusalem during the Second World War. After the war, the two started a long, fascinating and at times intense correspondence that ended only with Scholem's death. These letters, found in the Scholem archive in the National Library in Jerusalem, provide a rare perspective on the world and the approach of two leading historians of religion in the twentieth century. They also shed important new light upon Smith's discovery of a letter.